Study of Psychological Behaviour in State Level Batter and Bowlers (International Journal of Food and Nutritional Sciences, 2022)
Sports psychology is the scientific study of the mortal geste and mind, which helps athletes ameliorate performance by managing feelings and minimising the cerebral goods of injury and poor performance. It provides two major types of services performance improvement as a competitive strategy and comfort for colourful issues affecting the athlete. Competition is a specialised situation where athletes fight for supremacy and excellence. Psychology is the scientific study of mortal geste and mind, and sports psychology is a pearl of wisdom in which we study a sportsperson by observing, measuring and testing.